Production of particle board from sugarcane bagasse - Mohd Zamri Abdullah (Universiti Malaysia Perlis, 2008)
Particle board has been used widely in the furniture industry nowadays. In this study, the production of particle board from sugarcane bagasse is to reduce the waste of bagasse and air pollution. This study produced by combining rice husk with a Urea-Formaldehyde (UF) resin then pressed through a hot compression machine to form the particle board. The study of parameter is on the effect of ratio of binder. Several testing methods were used to characterize the particle board such as flexural test, moisture absorption test, thickness swelling test, Fourier Transform Infra-Red (FTIR) spectroscopy and Thermogravimetric Analysis (TGA). The result was compared with conventional particle board. From the flexural test, it shows that the more higher the UF percentage, the higher the flexural strength. The increase in UF binder percentage will increase the flexural strength of the particle board. The increase in the UF percentage will also decrease the water absorption of the particle board. This particle board from bagasse is suitable to be commercialized because it has a better mechanical properties and the raw material is cheap and abundant.